2011
DOI: 10.1182/blood-2010-12-324517
|View full text |Cite
|
Sign up to set email alerts
|

Megakaryocytes differentially sort mRNAs for matrix metalloproteinases and their inhibitors into platelets: a mechanism for regulating synthetic events

Abstract: Megakaryocytes transfer a diverse and functional transcriptome to platelets during the final stages of thrombopoiesis. In platelets, these transcripts reflect the expression of their corresponding proteins and, in some cases, serve as a template for translation. It is not known, however, if megakaryocytes differentially sort mRNAs into platelets. Given their critical role in vascular remodeling and inflammation, we determined whether megakaryocytes selectively dispense transcripts for matrix metalloproteinases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
130
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(136 citation statements)
references
References 56 publications
4
130
0
2
Order By: Relevance
“…25 In addition, platelet-derived lysophosphatidic acid was shown to support breast cancer metastasis and was identified as a potential therapeutic target by interfering with the recruitment of bone marrow-derived cells to angiogenic sites. 26 It was recently shown that megakaryocytes selectively transport mRNAs into platelets, allowing only a subset of RNAs to be transferred into platelets, 27 and Calverly et al identified a subset of megakaryocyte/platelet-derived mRNAs that are differentially expressed in lung cancer metastasis. 28 However, any role of tumorderived RNA in platelet biology and cancer remains to be investigated, and it remains unclear to what extent the transferred tumor-derived RNA can be functionally translated into proteins, thereby manipulating platelet function, as previously shown to occur in endothelial cells after uptake of tumor-derived microvesicles.…”
Section: Discussionmentioning
confidence: 99%
“…25 In addition, platelet-derived lysophosphatidic acid was shown to support breast cancer metastasis and was identified as a potential therapeutic target by interfering with the recruitment of bone marrow-derived cells to angiogenic sites. 26 It was recently shown that megakaryocytes selectively transport mRNAs into platelets, allowing only a subset of RNAs to be transferred into platelets, 27 and Calverly et al identified a subset of megakaryocyte/platelet-derived mRNAs that are differentially expressed in lung cancer metastasis. 28 However, any role of tumorderived RNA in platelet biology and cancer remains to be investigated, and it remains unclear to what extent the transferred tumor-derived RNA can be functionally translated into proteins, thereby manipulating platelet function, as previously shown to occur in endothelial cells after uptake of tumor-derived microvesicles.…”
Section: Discussionmentioning
confidence: 99%
“…RNA from human CD34-differentiated or fetal liver-derived proplatelet-producing megakaryocytes was isolated and prepped for deep sequencing as previously described (43)(44)(45). In brief, RNA was prepared for sequencing according to Illumina's (DNA vision) TruSeq kit V2 for poly-A RNA.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, these anuclear cells carry preselected messenger RNA that can be translated to protein and even have the capacity to divide within the circulation. [52][53][54] Functional anuclear granulocytes can be generated as either cytoplasts or motile cytokineplasts. 55,56 Applying heat to human neutrophils generates nuclear-free and granule-depleted PMN remnants capable of chemotaxis toward fMet-Leu-Phe.…”
Section: Anuclear Cellular Functionmentioning
confidence: 99%